Association between the C-reactive protein-albumin-lymphocyte index and cardiovascular incidence and mortality among patients with chronic kidney disease: a prospective study - Jiang, Chen; Zhou, Qi; Feng, Jian; Liu, Shuo; Fan, Miaomiao; Bai, Hao; Lin, Shujuan; Chen, Liyong (Frontiers in Immunology, 2026)
Background and aimThe recently developed C-reactive protein-to-albumin-to-lymphocyte (CALLY) index represents a novel composite biomarker that simultaneously reflects inflammatory status, immune competence, and nutritional adequacy. However, to date, there are limited evidence on whether CALLY index affects the cardiovascular disease (CVD) events in patients with chronic kidney disease (CKD). This prospective cohort study aimed to investigate the associations between the CALLY index and CVD incidence, all-cause and CVD-specific mortality in CKD patients from UK Biobank.MethodsThe CALLY index was calculated based on lymphocyte counts, serum albumin concentrations, and C-reactive protein (CRP) levels. The association between CALLY index and diverse CVD events were analyzed using multivariate Cox proportional hazards regression and restricted cubic splines (RCS) analysis.ResultsA total of 22,898 CKD patients were included. Compared to participants with lowest quartile of CALLY, those with highest quartile had decreased risk of incident overall CVD (HR: 0.70, 95%CI: 0.65-0.75), IHD (HR: 0.70, 95%CI: 0.63-0.78), MI (HR: 0.69, 95%CI: 0.57-0.83), stroke (HR: 0.74, 95%CI: 0.62-0.88), and all-cause (HR: 0.55, 95%CI: 0.51-0.61) and CVD-specific mortality (HR: 0.54, 95%CI: 0.44-0.66). RCS analysis showed the significant L-shaped dose-response relationships between CALLY index and CVD incidence and mortality outcomes, indicating a saturation effect.ConclusionThe moderate-to-high CALLY index was significantly associated with a reduced risk of CVD events-including IHD, MI, and stroke, as well as lower all-cause and CVD-specific mortality. These findings suggest that the CALLY index, which integrates inflammatory, nutritional, and immunological markers, may serve as a potential biomarker for risk stratification in patients with CKD. Future longitudinal studies incorporating repeated assessments would be valuable to better characterize the temporal trajectory of the CALLY index and its association with cardiovascular events and mortality in patients with CKD, thereby improving causal inference.